Thurgood Marshall papers - Marshall, Thurgood, 1908-1993.
Chiefly correspondence, case files, dockets, and other papers from Marshall's tenure on the U.S. Supreme Court (1967-1991); correspondence, administrative files, and other papers from his service (1961-1965) as a judge on the U.S. Court of Appeals (2nd Circuit); and correspondence and legal papers relating to his years as U.S. solicitor general (1965-1967). The papers reflect Marshall's advocacy for the civil rights of minority and impoverished individuals and of criminal defendants and his opposition to capital punishment. Correspondents include Benjamin O. Davis, John Doar, John Hope Franklin, Arthur J. Goldberg, Lyndon B. Johnson, J. Edward Lumbard, Adam Clayton Powell, Carl Thomas Rowan, and Roy Wilkins.
the Library's collections of the NAACP and the NAACP Legal Defense and Educational Fund.
Motion Picture, Broadcasting and Recorded Sound Division.
Lawyer, judge, solicitor general, and first African-American associate justice of the U.S. Supreme Court, appointed by President Lyndon B. Johnson in 1967.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Davis, Benjamin O. -- 1912-2002 -- Correspondence; Doar, John, -- 1921- -- Correspondence; Franklin, John Hope, -- 1915-2009 -- Correspondence; Goldberg, Arthur J. -- Correspondence; Johnson, Lyndon B. -- 1908-1973 -- Correspondence; Lumbard, J. Edward -- 1901- -- Correspondence; Powell, Adam Clayton, -- 1908-1972 -- Correspondence; Rowan, Carl T. -- 1925-2000 -- Correspondence; Wilkins, Roy, -- 1901-1981 -- Correspondence; United States. -- Court of Appeals (2nd Circuit); United States. -- Solicitor General; United States. -- Supreme Court; Capital punishment; Civil rights; Constitutional law -- United States; Criminals -- Civil rights -- United States; Law -- United States; Minorities -- Civil rights -- United States; Poor -- Civil rights -- United States; Jurists; Lawyers